Methodological approaches to formalized assessment of competitiveness in the system of strategic management accounting and economic assessment of construction enterprises - Zgalat-Lozynska, L.; Kosminsky, I.; Ivanova, T. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of methodological approaches to the formalized assessment of competitiveness and the scientific substantiation of their integration into the strategic management accounting system of construction enterprises. The relevance of the topic is due to the industry's need for tools that ensure an adequate response to risks in the context of macroeconomic instability. The authors systematized and analyzed key evaluation methods, in particular: calculation of market indices (market share, concentration index, Herfindahl-Hirschman Index), the qualimetric method, the principal criterion method, the distance calculation method, and the approach based on the theory of effective competition. It is established that the integration of formalized assessments directly into the strategic management accounting circuit is a key tool for ensuring sustainable development. This approach allows the transformation of the abstract concept of competitiveness into a manageable, quantitatively measurable parameter. The authors emphasize the significance that formalized methods for assessing competitiveness serve as an information platform for making informed decisions regarding budgeting, pricing, selection of investment projects, and risk management, overcoming the limitations of traditional accounting, which records data post factum. Particular attention is paid to the qualimetric method, which, through a system of weighted criteria (cost, terms, quality, reputation), allows for a comprehensive comparative analysis of the enterprise's position relative to competitors. It is underlined that, despite higher labor intensity, formalized methods provide significantly higher accuracy and analytical depth compared to expert tools, such as SWOT and BCG analysis. The study reveals the problem of the detachment of theoretical assessment models from the practical needs of management accounting in construction enterprises. It is substantiated that the embedding of these assessments into a unified information system allows for the timely identification of both competitive advantages and weaknesses, creating a basis for proactive management and strengthening long-term market positions.